Penciptaan Kain Pantai Berbasis Ragam Hias Suku Nias dengan Teknik Batik Tulis - Fianti Rahmi Aceh; Misgiya Misgiya (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
The beach cloth works created apply Nias ornaments as a renewal idea to make them attractive and different from previous beach cloths. The aim is to find out the preservation activities of Nias ornaments in the cycle of batik-based beach cloths. Nias ornaments have certain symbolic meanings that are believed and trusted by the local community. Ornaments that are part of fine art by paying attention to the principles in applying Nias ornaments to the beach cloths created. The creation process is carried out by: 1. Data collection, 2. Determining ornaments as samples, 3. Designing digital-based motifs, 4. Transferring designs to primis mori cloth, 4. The canting process using liquid wax, 5. Coloring beach cloth, 6. Locking the color of the cloth using waterglass, 7. Removing wax by boiling and processing the cloth, 8. Drying the cloth until dry. The creation produced 12 different beach cloth works with innovations to preserve Nias ornaments, while at the same time socializing beach cloth as a typical souvenir of the Nias tribe through art exhibitions.